Kinship practices in Early Iron Age South-east Europe: genetic and isotopic analysis of burials from the Dolge njive barrow cemetery, Dolenjska, Slovenia. (April 2023) - Armit, Ian; Fischer, Claire-Elise; Koon, Hannah; Nicholls, Rebecca; Olalde, Iñigo; Rohland, Nadin; Buckberry, Jo; Montgomery, Janet; Mason, Philip; Črešnar, Matija; Büster, Lindsey; Reich, David
Abstract: Abstract : The burial of multiple individuals within a single funerary monument invites speculation about the relationships between the deceased: were they chosen on the basis of status, gender or relatedness, for example? Here, the authors present the results of aDNA and isotope analyses conducted on seven individuals from an Early Iron Age barrow at Dolge njive, south-eastern Slovenia. All seven individuals are close biological relatives. While the group composition suggests strict adherence to neither patrilineal nor matrilineal structures, the funerary tradition appears highly gendered, and family links through both the male and female lines seem important in structuring of the community. The results have implications for understanding of kinship and funerary practices in late prehistoric Europe.